STUDI TENTANG KINERJA APARATUR PEMERINTAH DALAM PELAKSANAAN PELAYANAN PUBLIK DI KANTOR KELURAHAN TANJUNG PALAS TENGAH KABUPATEN BULUNGAN - Feber, Wempi (DIA: Jurnal Administrasi Publik, 2019)
To find out the performance of government officials in the implementation of public services at the Tajung Palas Tengah Sub-district office in Bulungan Regency and to find out the supporting factors and hamper the performance of government officials in implementing public services at the Tajung Palas Tengah Village Office in Bulungan Regency. Type of qualitative descriptive research. Informants were Head of Village, Secretary of Kelurahan, Head of Government Office, Kasi Kessos and community economy Kasi empowered the community, and Community leaders were two people. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the performance of public services at the Tanjung Palas Tengah Sub-District office in Bulungan Regency has gone well. Productivity Kelurahan employees carry out duties in accordance with their respective duties, and are able to complete tasks in a timely manner in accordance with community demand. The performance shown by the obedience of the kelurahan employees in carrying out their tasks has gone well. Obedience includes obedience to time, kelurahan employee code of ethics, adherence to leadership, and obedience in completing tasks. Employee performance in cooperation is good. Cooperation supports the implementation of good service because it supports each other and shares work according to their duties and functions. Employees are responsible for serving the community. Supporting factors for public service performance at the Tanjung Palas Tengah Village office are the ability of employees to provide good public services. Cooperation with employees, cooperation supports the success of urban village officials in providing good public services.